Wanderlust 101: beginner’s odyssey / Efina Hamdan and Maizura Manshor - Hamdan, Efina; Manshor, Maizura (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The shackles of the movement control order have finally been lifted, setting the stage for an exhilarating global escapade. The World Toursim Organization (UNWTO) reported that 2022 witnessed the increase of international trevellers by 50% from the previous year. More than 900 million tourists travelled internationally, and Middle East happened to be the most favorite destination while Asia and the Pacific recorded as the least. Thanks to the digital age, choosing your next odyssey has never been easier. Social media platforms such as TikTok, Instagram, Twitter and Facebook have become virtualtreasure troves, teeming with tantalizing recommendations of awe-inspiring locales, delectable culinary delights and insta-worthy cafes. Your wanderlust can now be guided bythe collective wisdom of fellow explorers. Leave application – approved! Passport – checked! Bags – packed! Nothing beats the excitement of a planned trip to escape from the reality for a moment. There are two types of travellers in this world; one who planned way in advance– we’re talking about at least 6 months to a year of planning, and the other one who are more spontaneous and adventurous where traveling can be an impulse decision. Some travel for business, some travel for leisure and some travel to visit friends and relatives. No matter which type of traveller you are or for what reason, always spare sometimes to do some research and preparation prior to your journey. Here are some tips for you on how to have a worry-free traveling.